CLINICAL ASPECT OF NORMAL PRESSURE HYDROCEPHALUS: WHAT TO DO? A LITERATURE REVIEW - Nazwar, Tommy; Bal’afif, Farhad; Wardhana, Donny; Riskiyana, Riskiyana; Agustina, Kartika; Panjaitan, Christin (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Normal pressure hydrocephalus (NPH) is a medical condition characterized by the enlargement of brain ventricles and associated clinical manifestations, including gait disturbance, cognitive impairment, and urinary incontinence. In many cases, NPH is often misdiagnosed or diagnosed late due to its symptoms closely resembling those seen in other neurological conditions. Therefore, a comprehensive understanding of the clinical characteristics of NPH is crucial. This article aims to present an in-depth literature review on the clinical aspects of NPH and offer valuable insights to clinicians regarding the appropriate approach to diagnosing and managing patients with NPH. Gait apraxia is usually the first symptom, followed by incontinence and cognitive impairment, particularly in attention and memory. The diagnosis of NPH follows specific criteria, classifying patients as